Management of Ma’had Integration into the Faculty of Islamic Religion: Pengelolaan Integrasi Ma’had ke dalam Fakultas Agama Islam - Febriantania, Putri; Istikomah (Journal of Islamic and Muhammadiyah Studies, 2025)
General background: Integration between Islamic educational institutions and universities is essential to strengthen quality and sustainability. Specific background: Ma’had Umar bin Al Khattab Sidoarjo, originally established by the Asia Muslim Charity Foundation, was later integrated into the Faculty of Islamic Studies at Muhammadiyah University of Sidoarjo (FAI UMSIDA). Knowledge gap: Previous studies have discussed pesantren–school integration, but little attention has been given to Ma’had–university integration from a management perspective. Aims: This study examines the management of Ma’had’s integration into FAI UMSIDA, focusing on human resources, curriculum, and student affairs. Results: Using a qualitative field research approach with observation, interviews, and document review, the study reveals that a semi-integration model was applied, allowing Ma’had to maintain autonomy while aligning with university systems. Novelty: The study introduces a management framework where semi-integration preserves institutional identity yet fosters structural coordination. Implications: Findings provide guidance for Islamic higher education institutions undergoing similar transitions and contribute to theoretical development in Islamic education management. Highlights: Semi-integration sustains Ma’had autonomy within university systems. Management covers HR, curriculum, and student affairs restructuring. Offers a framework for Islamic higher education integration. Keywords: Ma’had Integration; Islamic Education; Curriculum Management; Human Resources; Student Affairs